PEMBERDAYAAN DAN PENINGKATAN POTENSI KEARIFAN LOKAL DAERAH, MELALUI PENGELOLAAN BADAN USAHA MILIK DESA - Hidayat, Ofi; Ramadhani, Muhammad Muthahari (Jurnal Riset Entrepreneurship, 2022)
BUM Desa as a quasi-public organization needs a special strategy because BUM Desa is branded as a state-owned company at the village level which is still synonymous with ineffective and inefficient institutions. The purpose of this study is to see how the strategy of the existence of BUM Desa in the era of competition and economic and digital openness is required to be able to develop and increase competitiveness, especially in Paser Regency which is a candidate for the gateway to the new capital city of Indonesia. The research method used is descriptive qualitative by taking BUM Desa which has developed, and which is still in the basic stage. The results showed that the implementation of the BUM DESA program was mainly in two villages that had two different levels, namely Modang Village and Padang Jaya Village. This is because Capacity Development in the business world has been running in Padang Jaya Village, this is the basis for being substantially superior because the Padang Jaya village government prioritizes processes and trust in the community and local wisdom and is supported by high village income (PAD Desa) in the village. that prioritizes local culture or MSMEs from the community. Based on the assessment of the classification of BUMDes development in Paser Regency, Padang Village BUMDes are in the "Developing" BUMDes category or arguably the only BUMDes that have progressed in Paser Regency compared to BUMDes in Modang Village which are still in the "Basic" category. The results showed that the level of success of the BUM DESA program in community economic empowerment can be seen from the level of community participation, income levels of BUM DESA members and the level of community welfare. In addition, the implementation of the BUM DESA program in Modang Village and Padang Jaya Village in empowering business entities received an explanation of strengthening Individual Capacity, namely in 3 aspects including Personality capacity development where BUMDesa Padang Jaya got a superior personality capacity than BUMDesa Modang, then Capacity Development in the world work, so that Padang Jaya Village is substantially superior because the Padang Jaya village government prioritizes process and trust in the community and local wisdom and is supported by the high village income (PAD Desa) in the village based on the classification assessment of BUMDesa's development in Paser Regency, which is included in the BUMDesa category. “Developing” or arguably the only advanced BUMDesa in Paser Regency compared to BUMDesa in Modang Village which is still in the “Basic” category.